Understanding and managing public organizations : essential texts for nonprofit and public leadership and management - Rainey, Hal G. 1946-; Fernandez, Sergio (Professor of Public Administration); Malatesta, Deanna (Wiley, 2021)
Discover the latest insights in organization theory from a comprehensive and masterful volume Understanding and Managing Public Organizations, 6th Edition provides readers with an authoritative reference for scholars, masters, and doctoral students in public management and public affairs programs in the United States and other nations. The 6th Edition of Understanding and Managing Public Organizations presents the latest research and insights from organization and management theory and their application to public organizations and the people in them. The book expands coverage from previous editions about organizational goals, performance and effectiveness, strategy, decision-making, structure and design, organizational change, operating environments, individuals and groups, motivation and work-related attitudes, leadership, teamwork, and more. Authors and professors Hal Rainey, Sergio Fernandez, and Deanna Malatesta provide new and expanded coverage of such topics as The context and distinctive character of public and nonprofit organizations, including expanded coverage of'publicness'and of the legal context including'state action'Performance management, measurement, organizational effectiveness, and managing for high performance Representative bureaucracy, workforce diversity, and performance Communication and information technology Employee engagement and empowerment, intrinsic motivation, self-determination theory, public service motivation, and positive organizational behavior resilience, self-efficacy, optimism, and hope Recent developments in theory and thought on leadership, including authentic leadership, shared leadership, servant leadership, and integrated leadership Design and process topics including red tape and green tape, administrative burdens, and organizational routines Theoretical perspectives such as behavioral theory of decision making, resource dependence theory, and others, and their implications for public and nonprofit organizations Advances in theory and practice about rapid developments in collaborative governance, organizational networks, partnerships, and contracting Since the book is used in courses for students in numerous public affairs programs, this new edition updates the Instructor's Guide, with new and revised PowerPoint slides, cases, exercises, and discussion and examination questions These materials, with the topics in the chapters, are designed to address the learning outcomes required by NASPAA accreditation requirements Belonging on the shelf of scholars and students in public affairs, as well as anyone interested in public management or organization theory, this new edition of Understanding and Managing Public Organizations provides an advanced and comprehensive enhancement to a widely used and compelling series of previous editions.- Resumé vydavatel